84 Association between gun owner attitudes and their behavior in private firearm sales. (5th May 2020) - Merrill-Francis, Molly; McGinty, Emma Beth; Barry, Colleen; Webster, Daniel; Crifasi, Cassandra
Abstract : Statement of Purpose: Federal government only regulates individuals 'in the business' of selling firearms, leaving private firearm sales unregulated unless action is taken at the state level. Private sellers are less likely than licensed dealers to conduct background checks and most guns used in crime originate from sales in unregulated markets. This study examines whether private sellers' attitude that it is the responsibility of a seller to ensure buyers passed a background check prior to making a sale is associated with them checking purchasers for eligibility on their last sale. Methods/Approach: This study uses data from a nationally representative, web-based survey of 1, 444 individuals who personally owned guns. Respondents who self-reported participating in the private market (N=238) were asked whether they had ensured purchasers were eligible to buy a firearm on their last private sale. Respondents were also asked to rate the extent to which they agreed it was a seller's responsibility to ensure purchasers had passed a background check. Logistic regression was used to test for differences in behaviors based on sellers' perception of responsibility for ensuring purchaser eligibility. Results: Just 44% of respondents checked purchasers for eligibility on their last private sale. Less than half (46%) of private sellers agreed that it is seller responsibility to ensure purchasers passed a background check. Agreement was significantly associated with reporting ensuring purchasers were eligible to own a firearm on their last private sale (58% to 36%). Conclusion: A low number of background checks in the private market are occurring. Increasing sellers' feelings of responsibility may increase background and permit checks in the private market. Significance and Contributions to Injury and Violence Prevention Science: Our findings suggest that programs or campaigns to increase private sellers' feelings of responsibility may increase the number of background checks conducted in the private market.